2006
DOI: 10.1111/j.1525-1314.2006.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of H2O content in a polymetamorphic terrane: the Plattengneiss Shear Zone (Koralpe, Austria)

Abstract: The Koralpe of the Eastern European Alps experienced high-temperature/low-pressure metamorphism (650°C and 6.5 kbar) during the Permian and eclogite facies metamorphism (700°C and 14 kbar) during the Eo-Alpine (Cretaceous) metamorphic event. In the metapelitic Plattengneiss shear zone that constitutes much of the Koralpe, the second metamorphism caused only partial re-equilibration of the assemblages formed during the first metamorphism. It is shown here that the Eo-Alpine mineral assemblage, garnet + biotite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 30 publications
(61 reference statements)
2
63
0
Order By: Relevance
“…In this regard the KMZ differs from most other exhumed and active continental retrograde shear zones for which high fluid/rock ratios have been suggested (Kerrich et al, 1977;Etheridge et al, 1983; or for which high fluid pressures are inferred (Rice, 1992;Ozacar and Zandt, 2009). It consequently appears that retrograde shearing can be sustained under a variety of fluid regimes, from dry and entirely fluid absent (Tenczer et al, 2006), through low-volume fluid presence such as described here, to examples where shear zones are inundated and dominated by fluid. There is also a range in cases from where high fluid pressures are sustained by a combination of high fluid volumes and low permeability, to shear zones where either low fluid volumes or high permeability prevent the build-up of high fluid pressures.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In this regard the KMZ differs from most other exhumed and active continental retrograde shear zones for which high fluid/rock ratios have been suggested (Kerrich et al, 1977;Etheridge et al, 1983; or for which high fluid pressures are inferred (Rice, 1992;Ozacar and Zandt, 2009). It consequently appears that retrograde shearing can be sustained under a variety of fluid regimes, from dry and entirely fluid absent (Tenczer et al, 2006), through low-volume fluid presence such as described here, to examples where shear zones are inundated and dominated by fluid. There is also a range in cases from where high fluid pressures are sustained by a combination of high fluid volumes and low permeability, to shear zones where either low fluid volumes or high permeability prevent the build-up of high fluid pressures.…”
Section: Discussionmentioning
confidence: 80%
“…In the absence of rehydration, the rocks would have retained their (low) fluid content and granulite mineralogy from peak metamorphic conditions and experienced shearing and reworking under fluid-absent conditions (Guiraud et al, 2001;White and Powell, 2002;Tenczer et al, 2006;Diener et al, 2008). If this were the case, the samples would have consisted of orthopyroxene-bearing assemblages and would have grown garnet at the P -T conditions of shearing (450-480 • C and M H 2 O < 3 − 5 mol %; Fig.…”
Section: Fluid Regime Fluid Source and Infiltration Mechanismsmentioning
confidence: 99%
“…The multivariant peak assemblage fields of samples T18 and T29 overlap with the 1 σ error ellipses of calculated av PT and the av P for the same samples consistent with peak metamorphic conditions of ~700 °C and 12–13 kbar, consistent with previous estimates (e.g. Stüwe, ; Stüwe & Powell, ; Gregurek et al ., ; Tenczer & Stüwe, ; Tenczer et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous workers have demonstrated that is it an extremely powerful and useful method for providing detailed P-T-X information for a variety of metamorphic environments (e.g. Powell et al, 1998;Vance and Mahar, 1998;White et al, 2001;Cononolly and Petrini, 2002;White et al, 2003;Zeh et al, 2004;Harris et al, 2004;White et al, 2004;Evans, 2004;Johnson and Brown, 2004;Pelletier et al, 2005;White et al, 2005;Kelsey et al, 2005;Stipska and Powell, 2005;Zeh et al 2005a,b;Konrad-Schmolke et al, 2006;Tenczer et al, 2006;Dziggel et al, 2006;White et al, 2007;Diener et al, 2007;Powell and Holland, 2008;White et al, 2008;Millonig et al, 2008;Diener et al, 2008;Kelsey et al, 2008;Mahan et al, 2008). A recent paper by Powell and Holland (2008) discusses at the length the advantages and disadvantages of a pseudosection approach in comparison to a conventional thermobarometric approach.…”
Section: Pseudosection Thermobarometry Versus Conventional Thermobaromentioning
confidence: 99%